Potential of Madura Island’s Local Wisdom as a Contextual Learning Resource for Chemistry Concepts in Junior Secondary Science Education - Ibnul Mubarok; Laila Khamsatul Muharrami; Fenia Revalina; Putri Farhanah Sudirman (CV Rena Cipta Mandiri, 2026)
Madura Island is one of Indonesia’s islands rich in local wisdom. However, research is needed to integrate it as a learning resource in chemistry education. This study aims to examine the potential of Madura Island’s local wisdom as a source of contextual teaching materials in chemistry education at the secondary school level. A literature review method was employed, involving a qualitative descriptive analysis of 12 relevant articles as well as additional observational data regarding local wisdom that has not been previously discussed in prior research. The findings indicate that various forms of Madura’s local wisdom, including traditional herbal medicine, traditional food, traditional crafts, and salt production, contain rich scientific concepts that can be directly mapped into the chemistry curriculum, particularly topics such as pure substances and mixtures, elements and compounds, food additives, and chemical reactions. These resources align with the Merdeka Curriculum’s emphasis on contextual and student-centered learning and have demonstrated high validity and positive student responses when developed into instructional materials. It is recommended that future research develop a structured framework for ethnoscience-based chemistry teaching materials and conduct empirical studies to measure their direct impact on student learning outcomes and scientific literacy.